Knowledge and acceptance research of use of vine-branch in micro region of Gyöngyös - Gonda , Cecília (Applied Studies in Agribusiness and Commerce, 2012)
Significant quantity of renewable plant biomass comes into existence in Hungary year by year. Nowadays there are different wellknow possibilities for utilization. However these methods are not widely accepted. The most important obstacle is frequently caused by lack of knowledge of farmers. Without the necessary information the farmers become distrustful, and in many cases significantly decrease the efficiency of reclamation. Targeted communication method should be used to improve the rates of utilization. It should include appropriate content to their knowledge. This study research the knowledge and the acceptance of vine-branch utilization circle of wine-grower in micro region of Gyöngyös by questionnaire survey. We will know why the use of by-products has not spreaded yet circle of wine-grower and where they get their information from. The typically fragmented farms do not utilize because they do not know the process for doing or other people cultivate their vine-yard so they have not necessary machine. The questionnaire ask the farmers they want to offer their vine-branch a user factory.The questionnaires was completed by personal request. The reason of methods was the bigger rate of query. The questionnaire include question about the farm, the use of vinebranch and data of farmers. The villages were asked the rates of wine-grower. The aim of the research the rational utilize of by-product by wine-growers year by year. With the results of questionnaire survey we can inform the farmers with the appropriate method about the necessary knowledge.